Action Research for Quality Development in Rural Education in Scotland - Judith W. George (Journal of Research in Rural Education, 1996)
The professional development ofteaching staffis a critical issue for all educational institutions. In the UK, the focus ofquality assurance and assessment has been articulating the criteria of excellent performance, collecting appropriate data, and producing a self-judgement. This has beenchallenging, particularly in the context ofdistance educati n. Rural .tutors in the UK Open University, working in the Highlands and Islands of Scotland, feel that their isolation from colleagues makes it very difficultfor them to be certain ofthe benchmarks ofgood work. Their uncertainty has made them all the more interested in exploring ways of assessing their work in terms of insights into the learning experience of their students. This article describes the Action Research Programme thai the Open University in Scotlcmd has been running to provide tutors with the tools ofsuch evaluation.